2021
DOI: 10.1088/0256-307x/38/2/026401
|View full text |Cite
|
Sign up to set email alerts
|

Self-Similarity Breaking: Anomalous Nonequilibrium Finite-Size Scaling and Finite-Time Scaling

Abstract: Symmetry breaking plays a pivotal role in modern physics. Although self-similarity is also a symmetry, and appears ubiquitously in nature, a fundamental question arises as to whether self-similarity breaking makes sense or not. Here, by identifying an important type of critical fluctuation, dubbed ‘phases fluctuations’, and comparing the numerical results for those with self-similarity and those lacking self-similarity with respect to phases fluctuations, we show that self-similarity can indeed be broken, with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 53 publications
6
32
0
Order By: Relevance
“…1(d) and 1(e) around 𝑇c, though far away from it, the collapses are not quite good near the peaks where fluctuations are large as expected. [93,95] Similar results are obtained for 𝒯 = 15. [78] This is reasonable once the driven time is shorter than the cutoff memory time so that the latter becomes sub-leading.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…1(d) and 1(e) around 𝑇c, though far away from it, the collapses are not quite good near the peaks where fluctuations are large as expected. [93,95] Similar results are obtained for 𝒯 = 15. [78] This is reasonable once the driven time is shorter than the cutoff memory time so that the latter becomes sub-leading.…”
supporting
confidence: 82%
“…[67] FTS has been successfully applied to many systems to efficiently study their equilibrium and nonequilibrium critical properties. [13,[67][68][69][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] Here, we change the temperature 𝑇 through 𝜏 = 𝑇 −𝑇c = 𝑅𝑡 ′ [70] and choose 𝑅 as a variable in place of 𝑡 ′ . Accordingly, Eq.…”
mentioning
confidence: 99%
“…We now present the FTS of the entanglement entropy S in real-time driving. We will not consider effects of phase ordering [78], since it has been shown that once the extrinsic self-similarity of the so-called phases fluctuations is considered, critical scaling is good down to quite low temperatures [114,115]. In the real-time evolution, the correlation length does not converge and we cannot study its scaling unfortunately.…”
Section: B Fts With Finite Entanglementsmentioning
confidence: 99%
“…Recently [86,87], through studying the whole driving dynamics and hence the whole scaling functions rather than just at the critical point of the 2D Ising model, we discovered that the FTS and the FSS of some observable quantities are violated either in heating or in cooling even in their respective FTS and FSS regimes. Such anomalous scaling were found to originate from a novel source, the extrinsic self-similarity breaking of the so-called phases fluctuations.…”
Section: Introductionmentioning
confidence: 99%